Strategi Kantor Kementrian Agama dalam Penguatan Moderasi Beragama di Kalangan Masyarakat - Jupri Naldo; Agnysh Septya Nyngrum; Syafrida Aslami; Adinda Al Husna Br Simbolon; Azizah Sofiana; Fikri Ahmadi (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the strategies of the Ministry of Religious Affairs Office in strengthening religious moderation among the community and to comprehensively identify the supporting and inhibiting factors in its implementation. Religious moderation is a strategic issue in maintaining harmony, tolerance, and social integrity amid the increasing complexity of religious and cultural diversity in Indonesia. This study uses a qualitative method with a descriptive approach through interviews, observations, and documentation as data collection techniques to obtain in-depth and relevant information. The findings indicate that the strategies implemented include strengthening religious literacy through outreach and guidance activities, cross-sector collaboration with religious leaders and local governments, optimizing the role of religious instructors, and utilizing social media as an effective means of public education. In addition, fostering the younger generation through interfaith dialogue programs and inclusive religious activities serves as a preventive measure to counter radicalism and intolerance. The challenges faced include limited human resources and resistance from certain community groups toward religious moderation programs. Overall, the strategies implemented are considered fairly effective in fostering tolerant, inclusive, and harmonious attitudes within society.